Prove that $\cot x \cot 2 x-\cot 2 x \cot 3 x-\cot 3 x \cot x=1$
$L.H.S.$ $=\cot x \cot 2 x-\cot 2 x \cot 3 x-\cot 3 x \cot x$
$=\cot x \cot 2 x-\cot 3 x(\cot 2 x+\cot x)$
$=\cot x \cot 2 x-\cot (2 x+x)(\cot 2 x+\cot x)$
$=\cot x \cot 2 x-\left[\frac{\cot 2 x \cot x-1}{\cot x+\cot 2 x}\right](\cot 2 x+\cot x)$
$\left[\because \cot (A+B)=\frac{\cot A \cot B-1}{\cot A+\cot B}\right]$
$=\cot x \cot 2 x-(\cot 2 x \cot x-1)=1=R .H .S.$
The value of $\tan 81^{\circ}-\tan 63^{\circ}-\tan 27^{\circ}+\tan 9^{\circ}$ is
If $x = \cos 10^\circ \cos 20^\circ \cos 40^\circ ,$ then the value of $x$ is
If $\tan \alpha = \frac{1}{7}$ and $\sin \beta = \frac{1}{{\sqrt {10} }}\left( {0 < \alpha ,\,\beta < \frac{\pi }{2}} \right)$, then $2\beta $ is equal to
$(\sec 2A + 1){\sec ^2}A = $
$\tan \frac{A}{2}$ is equal to